Aucuboside Inhibits the Generation of Th17 Cells in Mice Colitis - Mei, Chenxue; Wang, Xiao; Meng, Fanxiang; Zhang, Xiaoqing; Chen, Ling; Yan, Siqi; Xue, Junxiu; Sun, Xun; Wang, Yuanyuan (Frontiers in Pharmacology, 2021)
Aucuboside is an iridoid glycoside extracted from traditional Chinese medicine such as Rehmannia glutinosa, enjoying a wide range of biological activities including antioxidant, anti-aging, anti-inflammatory, and anti-fibrotic effects. The effects of aucuboside on inflammatory bowel disease (IBD) was not studied. In this study, the effects of aucuboside on generation of foxp3+ regulatory T (Treg) cells and IL-17-producing T helper (Th17) cells in colitis was studied. A mouse colitis model was established by intracolonic administration of 2,4,6-trinitrobenzene sulfonic acid (TNBS) to mimic human IBD. The generation of Treg and Th17 cells was evaluated by flow cytometry. Aucuboside significantly alleviated colitis symptoms including weight loss, high disease activity index, and inflammatory responses. The generation of Th17 cells in colitis was significantly inhibited by aucuboside, which is accompanied with suppression of IL-17 expression. In Raw264.7 cells, LPS induced increase in IL-17 expression was also suppressed by aucuboside, which was significantly blocked by RORγt inhibitor sr2215. In addition, the decreased Treg cell proportion was also partially reversed by aucuboside, which may be a reflect of aucuboside induced inhibition of Th17 cells. This previously unrecognized immunoregulatory function of aucuboside may have clinical applications for IBD.